Assessing the impact of aquaculture in small dams in Ghana's North-East Region: early results and lessons - Zane, Giulia; Appiah, Sarah; Buisson, Marie-Charlotte; Bosompem, Richeal Akosua; Asmah, R.; Mensah, E. T. D.; Ahiah, L. A. (International Water Management Institute, 2025)
An aquaculture pilot started under the CGIAR Initiative on Aquatic Foods and continued under the CGIAR Sustainable Animal and Aquatic Foods (SAAF) Program demonstrated the feasibility of cage fish culture in small reservoirs in northern Ghana. It benefited over 50 youths, of whom one third were women, in four communities in the North-East region of Ghana. It provided training, capital, and inputs for one cycle of tilapia fish culture. A short-term evaluation of the pilot, conducted at the end of the first cycle of fish production, found that while the groups had gained some skills, they required further capacity building, especially to improve production efficiency, add value, and develop a stronger sense of ownership. Importantly, introducing aquaculture did not disrupt other water uses in the reservoirs and helped increase the availability of affordable fish in the communities, contributing to more diverse diets.